2012
DOI: 10.1111/gcb.12029
|View full text |Cite
|
Sign up to set email alerts
|

How interactions between microbial resource demands, soil organic matter stoichiometry, and substrate reactivity determine the direction and magnitude of soil respiratory responses to warming

Abstract: Recent empirical and theoretical advances inform us about multiple drivers of soil organic matter (SOM) decomposition and microbial responses to warming. Absent from our conceptual framework of how soil respiration will respond to warming are adequate links between microbial resource demands, kinetic theory, and substrate stoichiometry. Here, we describe two important concepts either insufficiently explored in current investigations of SOM responses to temperature, or not yet addressed. First, we describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 107 publications
(175 reference statements)
6
114
1
Order By: Relevance
“…Thus, thermal adaptation of soil respiration involved weaker response of mass-specific respiration to temperature change (Atkin and Tjoelker, 2003). Our results were supported by previous findings demonstrating that long-term warming can change the mechanisms of SOM turnover (Billings and Ballantyne, 2013).…”
Section: Lasting Effect On Soil Co 2 Effluxsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, thermal adaptation of soil respiration involved weaker response of mass-specific respiration to temperature change (Atkin and Tjoelker, 2003). Our results were supported by previous findings demonstrating that long-term warming can change the mechanisms of SOM turnover (Billings and Ballantyne, 2013).…”
Section: Lasting Effect On Soil Co 2 Effluxsupporting
confidence: 90%
“…Second, warming may increase microbial activity, leading to acceleration of SOM decomposition. This acceleration may come from long-term (Billings and Ballantyne, 2013) or temporary thermal adaptation of the microbial community to the warmer conditions (Bradford, 2013). An increasing number of studies have shown that warming changes microbial community structure, and warming increases the rate of enzymaticallycatalyzed reactions up to a temperature optimum (Wallenstein and Weintraub, 2008;Burns et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The response of enzymatic SOM degradation to temperature also depends on half-saturation (K m ) constants, which may respond to temperature in a manner that offsets SOM losses associated with V max responses (German et al 2012). Enzyme-specific thermal sensitivities have important implications for our understanding of the cycling of different nutrients and organic matter of different complexity under elevated temperatures (Allison et al 2010;Billings and Ballantyne 2012). While more controlled experiments are required to resolve the mechanism involved, the apparent site-acclimation of specific enzyme Q 10 responses has important ecological consequences.…”
Section: Generalisations Of Enzyme Temperature Sensitivities and Climmentioning
confidence: 99%
“…Other studies have also attempted to provide mechanistic explanations for the temperature dependence of SR (Davidson and others, 2006;von LĂŒtzow & Kögel-Knabner, 2009). In a review, Billings & Ballantyne (2013) examined the mechanisms that are linked to SR, and reported that temperature-induced changes in microbial community structure, microbial metabolic rates and catalytic rate of exo-enzymes may lead to a decline of SR as a response to an increase in the soil temperature.…”
Section: Introductionmentioning
confidence: 99%